Quantifying the grazing habits of beef cattle using remote sensing technology and assessing the composition of common shrubs in the West Coast Strandveld of South Africa - Hough, Wilmie (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.